Socio-demographic Profiles, Clinical Determinants, and Medication Adherence Patterns Among Hypertensive Adults at a Nigerian Teaching Hospital: A Cross-sectional Study - Abdul Ibraheem; Lateef Mustapha; Abitare Hope; Chinyere Nwosu; Lawal Badru; Zuliat Sanni; Nusirat Abdullateef (Journal of Family Medicine and Health Care, 2026)
Background: Hypertension is a leading cause of cardiovascular disease globally, but its management is frequently hindered by suboptimal medication adherence, which leads to poorly controlled blood pressure. While poor adherence is a well-documented challenge, a critical research gap exists in North-Western Nigeria regarding how the region's unique socio-cultural factors, such as high levels of informal education and polygamous family structures, influence patients' medication adherence in general outpatient settings. Objective: This study aimed to evaluate the socio-demographic profiles, clinical determinants, and medication adherence patterns among adult hypertensive patients attending a general outpatient clinic in a teaching hospital in North-Western Nigeria to provide context-specific epidemiological data for localized healthcare policies. Method: A hospital-based descriptive cross-sectional study was conducted among 130 adult hypertensive patients at the General Outpatient Clinic of the Federal Teaching Hospital Birnin Kebbi. Participants on antihypertensive medications for at least six months were selected using a systematic random sampling technique. Data were collected using a semi-structured questionnaire for socio-demographics, and the validated 8-item Morisky Medication Adherence Scale was utilized to evaluate adherence patterns. Additionally, blood pressure and Body Mass Index were measured and categorized. Data were analyzed using SPSS version 23, with chi-square tests used to determine statistical associations (p ≤ 0.05). Results: The participants had a mean age of 50.16 ± 11.09 years, and the majority (62.3%) were female. Medication adherence was exceptionally poor; according to the MMAS-8 scale, 74% of participants had low adherence, 23% had medium adherence, and only 3% had high adherence. There were no statistically significant associations between medication adherence patterns and socio-demographic variables. However, there was a statistically significant inverse relationship between the duration of hypertension treatment and medication adherence (p = 0.012). Participants treated for less than one year showed better adherence, while low adherence was exceedingly high among those treated for 1-5 years or longer. Furthermore, a significant majority (67.8%) of participants had uncontrolled blood pressure, and nearly half (43.1%) were obese. Conclusion: Medication adherence among adult hypertensive patients in North-Western Nigeria is alarmingly low, which severely undermines treatment efficacy and cardiovascular outcomes. The significant decline in adherence observed with longer treatment durations suggests pervasive treatment fatigue. To mitigate this, healthcare providers must implement continuous, patient-centered educational interventions and holistic lifestyle management strategies tailored to patients undergoing long-term therapy.